ASEAN Vision Beyond 2025 - Challenges and Strategies for an Inclusive Socio-Cultural Community - Arif Darmawan; David Aryodhi; Haliza Nurazizah; Randhi Satria; Virtuous Setyaka (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
The ASEAN Vision beyond 2025 aims to establish an inclusive socio-cultural community (ASCC), yet faces significant hurdles in its implementation. While ASEAN's commitment to socio-cultural integration is commendable, developing a cohesive regional identity remains a critical challenge due to historical grievances, extensive cultural diversity, and persistent socioeconomic inequalities among member states. Previous research has largely identified these issues separately without deeply analyzing their interconnections or the direct impact of economic and security dimensions on the socio-cultural community. This study addresses this research gap by specifically examining how economic disparities and security challenges, including external alliances such as AUKUS and the Quad, affect ASEAN's sociocultural cohesion and shared identity. This research aims to answer the following questions: (1) How do economic disparities among ASEAN member states influence the integration of the socio-cultural community? (2) In what ways do evolving security dynamics impact socio-cultural cohesion within ASEAN? The findings reveal that ASEAN’s sociocultural integration suffers significantly due to the lack of coherent policy synchronization between economic, political-security, and socio-cultural agendas, exacerbated by inadequate monitoring and enforcement mechanisms. Furthermore, the rise of external security alliances undermines ASEAN's centrality, causing internal fragmentation and weakening regional solidarity. To effectively achieve its vision beyond 2025, ASEAN must implement robust cross-sectoral coordination mechanisms, strengthen policy enforcement, promote inclusive participation, and reinforce its capacity to manage external security influences. Only through these targeted strategies can ASEAN build a truly unified and resilient socio-cultural community.